(untitled) (Movimenta (ISSN 1984-4298), 2023)
Patients with chronic renal failure (CRF) on hemodialysis (HD) have a high prevalence of sarcopenia leading an increase in morbidity and mortality. Objective: To investigate the prevalence of sarcopenia in CRF patients on HD. Cross-seccional study with CRF patients on HD where handgrip muscle strength was assessed by dynamometry, muscle mass by calf circumference (CC), physical performance by timed-up-and-go test (TUG) and quality-of-life by Kidney Disease Quality-of-life questionnaire. Twenty-two patients (54.5% women) aged 54.7 ± 11.9 years were evaluated. A prevalence of 27.2% of sarcopenia was identified in the sample. The criteria of reduced muscle strength (59.1%) was more predominant than the criteria of reduction in muscle mass (40.9%). TUG performance was adequate and was directly associated with age and with the scores in the domains of Cognitive Function, Physical Function and Energy/Fatigue of the quality-of-life questionnaire and inversely with the strength of the upper limb without the fistula. Approximately one third of HD patients have sarcopenia with predominance of changes in muscle strength.